2018
DOI: 10.1038/s41598-018-37364-2
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and perinatal outcomes for twin pregnancies in adolescent girls

Abstract: This was a nine-year retrospective cohort study to investigate obstetric and perinatal outcomes in a cohort of adolescent girls with twin pregnancies from a major Australian tertiary centre in Brisbane, Australia. The adolescent cohort was aged <19 years and the control group was aged 20–24 years. The total study cohort comprised of 183 women. Of these, the adolescent cohort contained 29 girls (15.8%) and the control group comprised of 154 women (84.2%). Adolescent girls were less likely to delivery via an ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The upper limit for this age cut off was intended to limit our comparison to younger adults at a standard risk for adverse birth outcomes. Adolescents and adults who delivered twins or triplets were excluded because of the known increased risk of birth complications with multiple gestations [ 29 , 30 ]. Data were not collected on deliveries that occurred prior to arriving to the hospital, infants transferred from an outside hospital after delivery, or deliveries before 24 weeks gestational age (classified as miscarriage in Botswana).…”
Section: Methodsmentioning
confidence: 99%
“…The upper limit for this age cut off was intended to limit our comparison to younger adults at a standard risk for adverse birth outcomes. Adolescents and adults who delivered twins or triplets were excluded because of the known increased risk of birth complications with multiple gestations [ 29 , 30 ]. Data were not collected on deliveries that occurred prior to arriving to the hospital, infants transferred from an outside hospital after delivery, or deliveries before 24 weeks gestational age (classified as miscarriage in Botswana).…”
Section: Methodsmentioning
confidence: 99%
“…In terms of preterm delivery, the literature included three more studies on adolescent twin pregnancies. 14,15,35 In the study of Blake and Lee involving 50 adolescent pregnant women with twins, no significant difference was found between the adolescent and control groups in terms of preterm labor (<37 weeks). 14 Robson et al studied 29 adolescent twin pregnancies and investigated preterm labor (<37 weeks), advanced preterm labor (28-32 weeks), and very advanced preterm labor (28 weeks).…”
Section: Discussionmentioning
confidence: 93%
“…14 Robson et al studied 29 adolescent twin pregnancies and investigated preterm labor (<37 weeks), advanced preterm labor (28-32 weeks), and very advanced preterm labor (28 weeks). 15 Their study found that adolescent twin pregnancies had a higher risk only in terms of very advanced preterm labor (<28 weeks). Branum classified deliveries at <33 weeks as very preterm births and found this rate significantly higher in adolescent twin pregnancies.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations